2018
DOI: 10.1037/abn0000332
|View full text |Cite
|
Sign up to set email alerts
|

Romantic involvement: A protective factor for psychological health in racially-diverse young sexual minorities.

Abstract: Sexual minority youth experience elevated rates of internalizing disorders; it is, therefore, important to identify protective factors that decrease risk for psychological distress in this population. In this study, we examined whether involvement in a romantic relationship, a well-established protective factor for mental health among heterosexual adults, is also protective for young sexual minorities. Using eight waves of data provided by a community sample of 248 racially diverse sexual minority youth (ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 75 publications
(132 reference statements)
12
73
6
1
Order By: Relevance
“…Instead, regarding the higher levels of anticipated binegativity in younger participants, it is plausible to hypothesize that older bisexual individuals have had more time to integrate their identity within the self-concept, developing competencies that allow them to buffer the negative effects of stigma on health (Van Wagenen et al 2013). Furthermore, we found that being older, more educated, and being in intimate relationships were associated with a better mental health, confirming previous studies highlighting the protective role against psychological distress of such factors (e.g., Fredriksen-Goldsen et al 2014;Van Wagenen et al 2013;Whitton et al 2018). Finally, we found that a very high percentage of participants met the clinical cut-off of both depression (78.7%) and anxiety (68.2%).…”
Section: Discussionsupporting
confidence: 88%
“…Instead, regarding the higher levels of anticipated binegativity in younger participants, it is plausible to hypothesize that older bisexual individuals have had more time to integrate their identity within the self-concept, developing competencies that allow them to buffer the negative effects of stigma on health (Van Wagenen et al 2013). Furthermore, we found that being older, more educated, and being in intimate relationships were associated with a better mental health, confirming previous studies highlighting the protective role against psychological distress of such factors (e.g., Fredriksen-Goldsen et al 2014;Van Wagenen et al 2013;Whitton et al 2018). Finally, we found that a very high percentage of participants met the clinical cut-off of both depression (78.7%) and anxiety (68.2%).…”
Section: Discussionsupporting
confidence: 88%
“…Being in a romantic relationship appears to reduce drinking among all SGM youth, and reduce use of drugs other than marijuana among those who identify as gay or lesbian. Together with evidence that romantic involvement has psychological benefits in this population, reducing distress associated with victimization they experience related to their minority sexual identity (Whitton et al, 2018), these results support initiatives to promote healthy relationships among SGM youth. Efforts to encourage dating among SGM (e.g., through planned LGBT-focused social events), and to teach healthy relationship skills (Mustanski et al, 2015), may ultimately help reduce the mental health and substance use disparities they face.…”
Section: Discussionsupporting
confidence: 52%
“…Specific sexual identities may also influence how romantic involvement affects substance use. Although dating is associated with better psychological health among gay and lesbian individuals, among bisexuals it is associated with greater risk for anxiety disorders (Feinstein et al, 2016) and more psychological distress (Whitton et al, 2018). These differences may be attributable to unique stressors bisexuals face when involved in romantic relationships, including invalidation of their bisexual identity by others who assume they are lesbian/gay or heterosexual based on their current partner’s gender (Dyar et al, 2014) and pressure from non-bisexual partners to change their sexual identity (Bostwick and Hequembourg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research among both sexual minority and general samples of youth has demonstrated the positive effect of serious partnerships on emotional wellbeing. [42][43][44] In addition, having a regular partner increases availability of sex, which may then increase global satisfaction with one's sex life. It is also possible that those with higher interest in sexual activity may seek out a serious partner so that sex is more readily available.…”
Section: Discussionmentioning
confidence: 99%